The Strategy of Islamic Religious Extenders Based on Religious Moderation: Study: Islamic Religious Counselor at KUA East Bekasi - Marpuah , Marpuah (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
Religious Counselors as the front guard in the Ministry of Religion, the phenomenon of cultural diversity requires counselors to understand multicultural knowledge and awareness. So that they have the competence to deal with differences, no matter how small the differences between target groups. Extension workers need to improve their perception, equip themselves with knowledge about cultural diversity. Understand the forms of discrimination, stereotypes and racism that often occur in people's lives. In a multicultural society, extension workers are expected to be facilitators of change and experts in resolving conflict. As well as conducting consultations with related parties to increase harmony within the target group. Because awareness and understanding of cultural diversity (multiculturalism), especially religious diversity, is increasingly needed by society. The aim of this research is to describe the preaching strategy of Religious Counselors based on religious moderation in the KUA of East Bekasi Regency. Data collection instruments through: Observation, Interviews, and Documentation. The results of the research can be concluded that the religious moderation-based da'wah strategy at KUA East Bekasi has been implemented by functional religious instructors and non-civil servant instructors, especially delivering material related to religious harmony, de-radicalization and tolerance, as well as delivering moral messages using religious language to their congregation, which is oriented towards on: Tawazun, Tasamuh, and Tawasuth. The delivery method is through approaches: Informative, Educative, Consultative and Advocative